Мифы, легенды и сказки удмуртского народа - Кралина Надежда Петровна (Удмуртия, 2019)
Экземпляры: ф.4 (20200825) / Инвентарный номер: 52561 / Цена: 600.00 / Авт.знак: М 68 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм)